Demographic Profile of the English-speaking Communities in the Administrative Region of Côte-Nord & MRC Sept-Riviéres - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profiles of English-speaking Communities : RTS de la Côte-Nord & RLS de Sept-Îles (0914) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS de Sept Iles (0903) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Community Portrait : Sept-Îles - Richardson, Mary (Community Health and Social Services Network (CHSSN), 2012)
In 2009, the Community Health and Social Services Network (CHSSN) concluded an agreement with Quebec’s Institut national de santé publique (INSPQ) to develop knowledge on the English-speaking population of Quebec as part of a program concerning health projects for official language minority communities. Gaining a better understanding of English-speaking communities in Quebec is one of the objectives of that collaboration, and it is explored here through the lens of community development.

Coasters Association Informer - Coasters Association (1996)